Primary intraosseous CD9-positive B-cell lymphoblastic lymphoma of the maxilla affecting a pediatric patient: Immunohistochemical and in situ hybridization analysis - Silveira, Heitor Albergoni [UNESP]; Sousa, Lucas Moura; Silva, Evânio Vilela [UNESP]; Almeida, Lana Kei Yamamoto; Sverzut, Cassio Edvard; Trivellato, Alexandre Elias; León, Jorge Esquiche (Elsevier, 2020)
Lymphoblastic lymphoma (LBL) is a clinically aggressive disease, representing approximately 2% of all non-Hodgkin lymphoma cases. In the oral and maxillofacial (OMF) region, approximately 39 cases, diagnosed as LBL, acute lymphoblastic leukemia (ALL) or ALL/LBL, have been reported to date. Noteworthy, the CD9 expression, which indicates a poor outcome in ALL, has not been reported in LBL and lymphoblastic neoplasms of the OMF region. Herein, we report an additional maxillary intraosseous B-cell LBL, affecting a 14-year-old girl, which also showed positivity for CD9, Bcl-6 and MUM1/IRF4. Aiming at diagnostic and prognostic criteria, further studies focusing CD9 expression in LBL is recommended.
Keywords: Acute lymphoblastic leukemia; CD9; Immunohistochemistry; In situ hybridization; Intraosseous lymphoma; Lymphoblastic lymphoma; Oral and maxillofacial region; Pediatric patient